A novel form of glycolytic metabolism‐dependent cardioprotection revealed by PKCα and β inhibition. (26th July 2019) - Brennan, Sean; Chen, Shen; Makwana, Samir; Martin, Christopher A.; Sims, Mark W.; Alonazi, Asma S.A.; Willets, Jonathan M; Squire, Iain B.; Rainbow, Richard D.
Abstract : Key points: Acute hyperglycaemia at the time of a heart attack worsens the outcome for the patient. Acute hyperglycaemia is not limited to diabetic patients and can be due to a stress response in non‐diabetics. This study suggests that the damaging cardiac effects of hyperglycaemia can be reversed by selective PKC inhibition. If PKCα/β isoforms are inhibited, then high glucose itself becomes protective against ischaemic damage. Selective PKC inhibition may therefore be a useful therapeutic tool to limit the damage that can occur during a heart attack by stress-induced hyperglycaemia. Abstract: Hyperglycaemia has a powerful association with adverse prognosis for patients with acute coronary syndromes (ACS). Previous work shows that high glucose prevents ischaemic preconditioning and causes electrical and mechanical disruption via protein kinase C α/β (PKCα/β) activation. The present study aimed to: (i) determine whether the adverse clinical association of hyperglycaemia in ACS can be replicated in preclinical cellular models of ACS and (ii) determine the importance of PKCα/β activation to the deleterious effect of glucose. Freshly isolated rat, guinea pig or rabbit cardiomyocytes were exposed to simulated ischaemia after incubation in the presence of normal (5 mm ) or high (20 mm ) glucose in the absence or presence of small molecule or tat‐peptide‐linked PKCαβ inhibitors. In each of the four conditions, the following hallmarks of cardioprotection were recorded using electrophysiology or fluorescence imaging: cardiomyocyte contraction and survival, action potential stability and time to failure, intracellular calcium and ATP, mitochondrial depolarization, ischaemia‐sensitive leak current, and time to Kir 6.2 opening. High glucose alone resulted in decreased cardiomyocyte contraction and survival; however, it also imparted cardioprotection in the presence of PKCα/β inhibitors. This cardioprotective phenotype displayed improvements in all of the measured parameters and decreased myocardium damage during whole heart coronary ligation experiments. High glucose is deleterious to cellular and whole‐heart models of simulated ischaemia, in keeping with the clinical association of hyperglycaemia with an adverse outcome in ACS. PKCαβ inhibition revealed high glucose to show a cardioprotective phenotype in this setting. The results of the present study suggest the potential for the therapeutic application of PKCαβ inhibition in ACS associated with hyperglycaemia. Key points: Acute hyperglycaemia at the time of a heart attack worsens the outcome for the patient. Acute hyperglycaemia is not limited to diabetic patients and can be due to a stress response in non‐diabetics. This study suggests that the damaging cardiac effects of hyperglycaemia can be reversed by selective PKC inhibition. If PKCα/β isoforms are inhibited, then high glucose itself becomes protective against ischaemic damage. Selective PKC inhibition may therefore be a useful therapeutic tool to limit the damage that can occur during a heart attack by stress-induced hyperglycaemia.